Endothelium-Dependent Vasorelaxant Effect of Butanolic Fraction from Caryocar brasiliense Camb. Leaves in Rat Thoracic Aorta. (15th August 2012) - Oliveira, Lais Moraes de; Rodrigues, Aline Gabriela; Silva, Elaine Fernanda da; Cerqueira, Letícia Bonancio; Castro, Carlos Henrique; Pedrino, Gustavo Rodrigues; Carvalho, Maria Helena Catelli de; Pontarolo, Roberto; Costa, Elson Alves; Campos, Francinete Ramos; Filgueira, Fernando Paranaiba; Ghedini, Paulo César
Abstract : Caryocar brasiliense Camb. "pequi" is a native plant from the Cerrado region of Brazil that contains bioactive components reported to be antioxidant agents. Previous work has demonstrated that dietary supplementation with pequi decreased the arterial pressure of volunteer athletes. We found that the crude hydroalcoholic extract (CHE) of C. brasiliense leaves relaxed, in a concentration-dependent manner, rat aortic rings precontracted with phenylephrine, and that the butanolic fraction (BF) produced an effect similar to that of the CHE. Aortic relaxation induced by BF was abolished by endothelium removal, by incubation of the nitric oxide synthase inhibitor L-NAME, or the soluble guanylatecyclase inhibitor ODQ. However, incubation with atropine and pyrilamine had no effect on the BF-induced vasorelaxation. Moreover, this effect was not inhibited by indomethacin and tetraethylammonium. The concentration-response curve to calcium in denuded-endothelium rings was not modified after incubation with BF, and the vasorelaxation by BF in endothelium-intact rings precontracted with KCl was abolished after incubation with L-NAME. In addition, administration of BF in anesthetized rats resulted in a reversible hypotension. The results reveal that C. brasiliense possesses both in vivo and in vitro activities and that the vascular effect of BF involves stimulation of the nitric oxide/cyclic GMP pathway.